Young Stalin - Sebag Montefiore, Simon, 1965- (London Weidenfeld and Nicolson, 2007)
Stalin, like Hitler, remains the very personification of evil but also one of the creators of today's world. Simon Sebag Montefiore unveils the shadowy, adventurous journey of the Georgian cobbler's son who became the Red Tsar." "Born in poverty, scarred by his upbringing, exceptional in his studies, this charismatic but dangerous boy was hailed as a romantic poet and trained as a priest but found his mission as fanatical revolutionary. He became the mastermind of bank-robberies, protection-rackets, arson, piracy and murder yet he was, uniquely, part-intellectual, part-brigand. Surprisingly, he is also revealed as a scandalously prolific lover, leaving a trail of mistresses (varying from schoolgirls to noblewomen) and illegitimate children
Include Epilogue, Note, bibliography and Index
Keywords: Heads of state -- Soviet Union -- Stalin, Joseph, 1878-1953 -- Russia -- Politics and government -- Families